Improved effectiveness and safety of flexible ureteroscopy for renal calculi (<2 cm): A retrospective study - Chen, Shuqiu; Xu, Bin; Liu, Ning; Jiang, Hua; Zhang, Xiaowen; Yang, Yu; Liu, Jing; Sha, Guozhu; Zhu, Weidong; Chen, Ming (Canadian Urological Association Journal, 2015)
Introduction: We discuss the efficacy and safety of flexible ureteroscopy for renal calculi with a burden of <2 cm, as well as the prevention and treatment of complications. Methods: A total of 108 renal calculi with flexible ureteroscopy and holmium laser treatment were retrospectively analyzed. The stone-free rate was evaluated. The effectiveness, safety, surgical technique, incidence of complications, and relevant treatments were analyzed. Results: All patients underwent only one lithotripsy procedure. The success rate of flexible ureteroscopy was 97.2% (105/108). Among the 105 cases, the total lithotripsy success rate was 97.1% (101/105). The total stone-free rate after 8 weeks post-operation was 94.3% (99/105), the stone-free rate of the lower calyx was 85.7% (30/35); it was 98.6% (69/70) in the middle‒upper calyceal and renal pelvis. The incidence of complications was 12.9% (14/108). None of the patients had serious adverse outcomes. Conclusion: Flexible ureteroscopy represents an optimal treatment option for selected renal calculi with burden of <2 cm. The effectiveness and safety of flexible ureteroscopy can be further improved through reasonable preoperative evaluation and advances in surgical techniques, as well as a better understanding of the inducement and treatment of complications.